Odpowiedź:
zad 4
(5x - 3)/4 + 3 = 2x | * 4
5x - 3 + 3 * 4 = 4 * 2x
5x - 3 + 12 = 8x
5x - 8x = 3 - 12
- 3x = - 9
3x = 9
x = 9/3 = 3
b)
x - (2x + 3)/5 = 3 | * 3
3x - (2x + 3) = 3 * 3
3x - 2x - 3 = 9
x - 3 = 9
x =9 + 3 = 12
c)
4 - x/4 = 2x - 1/2 | * 4
4 * 4 - x = 2x * 4 - 1/2 * 4
16 - x = 8x - 2
- x - 8x = - 2 - 16
- 9x = - 18
9x = 18
x = 18/9 = 2
d)
2x/3 + 4 = (x + 2)/3 | * 3
2x + 4 * 3 = x + 2
2x + 12 = x + 2
2x - x = 2 - 12
x = - 10
e)
(3x - 2)/5 - 2 = x/5 | * 5
3x - 2 - 2 * 5 = x
3x - 2 - 10 = x
3x - x = 2 + 10
2x = 12
x = 12/2 = 6